Direct activation of GABAA receptors by substances in the organic acid fraction of Japanese sake. (1st January 2017) - Izu, Hanae; Shigemori, Kensuke; Eguchi, Masaya; Kawane, Shuhei; Fujii, Shouko; Kitamura, Yuji; Aoshima, Hitoshi; Yamada, Yasue
Highlights: Thirteen organic acids containing in sake showed the GABAA receptor agonist activity. Lactic acid showed high agonist activity on the GABAA receptor. The relations of the anti-anxiety, organic acids and the GABAA receptor. Abstract: We investigated the effect of substances present in Japanese sake on the response of ionotropic γ-aminobutyric acid (GABA)A receptors expressed in Xenopus oocytes. Sake was fractionated by ion-exchange chromatography. The fraction containing organic acids (OA fraction) showed agonist activities on the GABAA receptor. OA fractions from sake were analyzed by capillary electrophoresis time-of-flight mass spectrometry (CE-TOFMS). Of the 64 compounds identified, 13 compounds showed GABAA receptor agonist activities. Especially, l -lactic acid showed high agonist activity and its EC50 value was 37 μM. Intraperitoneal injections ofl -lactic acid, gluconic acid, and pyruvic acid (10, 10, and 5 mg/kg BW, respectively), which showed agonistic activity on the GABAA receptor, led to significant anxiolytic effects during an elevated plus-maze test in mice.